BRAF, A gatekeeper controlling endothelial permeability. (13th May 2019) - Declercq, Mathias; Treps, Lucas
Abstract : The RAF/MEK/ERK signal transduction pathway is commonly deregulated in cancer and is activated by various stimuli regulating a variety of cell responses. In wild‐type endothelial cells, upon permeability stimuli, ROKα, RAF1, BRAF, and RAP1 become activated, inducing a cascade of reactions resulting in F‐actin remodeling and increased cell permeability. Here, Dorard et al . showed that BRAF ablated cells had more RAF1/ROKα dimerization and relocalization to VE‐cadherin occurred, ultimately leading to less F‐actin content and reduced vessel permeability.